On the effect of aqueous Ca on magnesite growth – Insight into trace element inhibition of carbonate mineral precipitation. (1st April 2016) - Berninger, Ulf-Niklas; Jordan, Guntram; Lindner, Michael; Reul, Alexander; Schott, Jacques; Oelkers, Eric H.
Abstract: Motivated by the strong effect of aqueous Mg on calcite growth rates, this study used hydrothermal atomic force microscopy (HAFM) and hydrothermal mixed-flow reactor (HMFR) experiments to explore the effect of aqueous Ca on magnesite growth kinetics at 100 °C and pH ∼7.7. Obtuse step velocities on (1 0 4) surfaces during magnesite growth were measured to be 4 ± 3 nm/s at fluid saturation states, equal to the ion activity quotient divided by the equilibrium constant for the magnesite hydrolysis reaction, of 86–117. These rates do not vary systematically with aqueous Ca concentration up to 3 × 10 − 3 mol/kg. Magnesite growth rates determined by HAFM are found to be negligibly affected by the presence of aqueous Ca at these saturation states and are largely consistent with those previously reported in aqueous Ca-free systems by Saldi et al. (2009) and Gautier et al. (2015). Similarly, magnesite growth rates measured by HMFR exhibit no systematic variation on aqueous Ca concentrations. Rates in this study, however, were extended to higher degrees of fluid supersaturation with respect to magnesite than previous studies. All measured HMFR rates can be accurately described taking account the combined effects of both the spiral growth and two dimensional nucleation/growth mechanisms. Despite the lack of a clear effect of aqueous Ca on magnesite growth rates, Raman spectroscopy confirmed the incorporation of up to 8 mol percent of Ca 2+ into the growing magnesite structure.